A COMPARATIVE-CORRELATIONAL STUDY OF PERCEIVED SCHOOL CLIMATE AND SCHOOL LIFE SATISFACTION OF MIDDLE AND HIGH SCHOOL STUDENTS AT KING MONGKUT'S INSTITUTE OF TECHNOLOGY LADKRABANG INTERNATIONAL DEMONSTRATION SCHOOL - RAZ, FREDERICK; RAFAEL GONZALEZ GONZALEZ, ORLANDO (Scholar: Human Sciences, 2022)
The purpose of this research was to explore the difference in and the relationship between perceived school climate and school life satisfaction of middle and high school students at King Mongkut's Institute of Technology International Demonstration School. The sample of this study consisted of all the middle and high school students who were enrolled in the target school during the academic year 2020-2021. The School Climate Survey was used to measure students' level of perceived school climate, while the School Life Satisfaction Survey was employed to measure the level of students' school life satisfaction. After data collection was done, descriptive statistics (means and standard deviations) and statistical hypothesis testing (one-way ANOVA and correlational analysis using Pearson's correlation coefficient) were carried out to address the objectives and hypotheses of this study. On a scale of 1-5, with 5 being "very positive," no significant difference was found in middle school students' level of perceived school climate (which ranged from a low of 3.33 for Grade 6 to a high of 3.54 for Grade 7). Similarly, on a scale of 1-5, with 5 being "very high," no significant difference was found in middle school students' level of school life satisfaction (which ranged from a low of 3.46 for Grade 6 to a high of 3.73 for Grade 8). There was no significant difference in high school students' level of perceived school climate (which ranged from a low of 3.45 for Grade 9 to a high of 3.64 for Grade 11); however, a significant difference was found in high school students' level of school life satisfaction (which ranged from a low of 3.60 for Grade 9, to a high of 4.03 for Grade 12). A significant, strong, and positive relationship was found between the perceived school climate and the school life satisfaction for middle and high school students. Based on the findings of this study, recommendations are provided for students, teachers, school administrators, and future researchers.